Children’s Plight to Life of Poverty and Injustice Captured in F.H. Batacan’s Smaller and Smaller Circles - Magay, Ma. Veronica F.; Dimaano, Matilda H. (Universitas Sanata Dharma, 2024)
This research paper analyzes how children's experiences of poverty and injustice are imagined and articulated in F. H. Batacan's novel Smaller and Smaller Circles. By employing content analysis, passages and excerpts from the novel were identified and subjected to in-depth analysis using sociological and philosophical approaches to literary criticism. The study aims to explore the novel’s portrayal of the causes and effects of these experiences, and how it reflects the broader discourse on the morality of children's suffering. The findings reveal that the novel imagines children's experiences of poverty and injustice as resulting from a complex interplay of societal norms, such as generational responsibility, the culture of silence, and toxic masculinity. Institutional failures, including the church’s complicity, inefficient law enforcement, and barangay deficiencies, further exacerbate these conditions. Additionally, media and societal attitudes, particularly misplaced faith and victim blaming, contribute to the perpetuation of these harmful conditions. The novel portrays these imagined experiences as leading to psychosocial trauma, delayed or denied justice, delinquency, and even suicide. Through this portrayal, the novel positions itself within the discourse on the morality of children's suffering, raising questions about the ethical implications of these societal failures.